Household’s Willingness to Pay for Improved Water Supply Services in Mettu Town: An Assessment - S.N. Singh (Financial Markets, Institutions and Risks)
The purpose of the article is to analyze and determine the willingness of citizens to pay for improving the quality of water services (the income derived from the consumption of water services does not cover the costs of providing such services). The study focuses on Ethiopia’s metropolitan areas (including households in town Mettu), as it is the problem of financial scarcity in Ethiopia that is particularly relevant and access to water services is a key component in calculating the human poverty index for most developing countries. Based on a survey of 79 Mettu town households, it is justified that residents view water not as a public good but as an economic good, as they are prepared to pay for it. The survey concluded that an average of 69% of Mettu households are willing to pay for improved water quality, with household income, water supply satisfaction and supply price having a strong impact on households’ willingness to pay for improved water services. In particular, the older the locals are and the higher their income level, the more they are willing to pay for improved water quality and security of water supply. At the same time, rising levels of education in Mettu residents reduce their willingness to incur additional financial costs, more educated people view water services as a boon to the authorities. The results of the study proved that while providing local authorities with high quality water supply services, more than 80% of households are ready and able to pay for services at a price that exceeds the tariff rate for water supply costs. The article stated that increasing the quality of water supply services by increasing the amount of tariffs for water use will contribute to the growth of financial revenues of local authorities, which will ensure the provision of water supply in the required quantity and on a stable basis.